A decision makers’ guide to equitable sustainable agricultural intensification - Grabowski, Philip; Fischer, Gundula; Djenontin, I.N.S.; Zulu, L.; Kamoto, J.; Kampanje-Phiri, J.; Egyir, I.; Darkwah, A. (International Institute of Tropical Agriculture, 2022)
In many parts of the world, there is a clear need for investment in agriculture to counteract low yields and food insecurity. Focusing only on short-term production gains, however, through technologies such as improved seeds, irrigation, fertilizers and pesticides, increases risks to the environment and human health.